Engaging Anthropological Theory : A Social and Political History (New York: Routledge, 2025)
The updated third edition of this book critically reconsiders the history of anthropological theory. Covering key concepts and theorists in a lively style, Engaging Anthropological Theory examines the historical context of anthropological ideas and the contested nature of anthropology itself. The book illustrates how anthropological ideas about human diversity are rooted in historical conditions, including the West$1 (Bs relationship with colonized societies and the politics of scholarly inquiry itself. Exploring anthropological ideas in context helps students understand how they evolved and how they relate to society and history. This new edition pays close attention to non-canonical figures and scholars of color whose contributions are too often bypassed in disciplinary histories. Students and instructors will also appreciate the open-ended review questions for each chapter that stimulate critical thought and discussion. Extensively illustrated throughout, this engaging text moves away from the dry recitation of past viewpoints in anthropology and shows their continued relevance to modern life.s
Includes Index
Keywords: Anthropology$1 (BPhilosophys; Political anthropology; Anthropology$1 (BHistorys; Ethnology$1 (BPhilosophys